Treating Patients Like Athletes: Sports Science Applied to Parkinson's Disease - Bouça-Machado, Raquel; Venturelli, Massimo; Tinazzi, Michele; Schena, Federico; Ferreira, Joaquim J. (Frontiers in Neurology, 2020)
The evidence demonstrating the benefits of exercise is indisputable for healthy subjects, and more recently, it is growing for patients with Parkinson’s disease (PD). Due to its easy access, low cost, social facilitation and, above all, the symptomatic effect, clinical exercise may have a profound impact on PD management. Especially considering that in recent decades there have been no major advances from the pharmacological point of view. Despite this, clinical exercise use it stills limited by the existent flaws in the available evidence supporting its use and guiding its prescription as a therapeutic intervention in PD. We believe that a joint approach from the most relevant scientific and clinical fields is crucial to establish the use of clinical exercise in PD patients’ routine care. Therefore, in this viewpoint, we aim to highlight the importance of clinical exercise as a therapeutic intervention in PD, and particularly of the benefits of applying sports science principles to potentiate the use of clinical exercise as a therapeutic intervention in PD management.